2015
DOI: 10.1159/000381403
|View full text |Cite
|
Sign up to set email alerts
|

Addition of eGFR and Age Improves the Prognostic Absolute Renal Risk-Model in 1,134 Norwegian Patients with IgA Nephropathy

Abstract: Background: Predicting outcome in individual patients with IgA nephropathy (IgAN) is difficult but important. For this purpose, the absolute renal risk (ARR) model has been developed in a French cohort to calculate the risk of end-stage renal disease (ESRD) and death. ARR (0-3) is scored in individual IgAN patients based on the presence of proteinuria ≥1 g/24 h, hypertension, and severe histopathological lesions (1 point per risk factor). We have validated the ARR model in a Norwegian cohort of IgAN patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In their case series of 1, 134 patients in the Norwegian Kidney Biopsy Registry, Knoop et al reported a prevalence rate of hypertension of 36% among patients with IgA nephropathy [25]. Other studies regarding the prevalence rate of hypertension associated with IgA nephropathy reported similar values, as follows: 56% in a single-center study in the Czech Republic [26]; 58% among a study cohort of 478 Indian patients [27]; and 31% among 1155 Chinese patients [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their case series of 1, 134 patients in the Norwegian Kidney Biopsy Registry, Knoop et al reported a prevalence rate of hypertension of 36% among patients with IgA nephropathy [25]. Other studies regarding the prevalence rate of hypertension associated with IgA nephropathy reported similar values, as follows: 56% in a single-center study in the Czech Republic [26]; 58% among a study cohort of 478 Indian patients [27]; and 31% among 1155 Chinese patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect differences with regard to inclusion criteria across different studies. For example, Knoop et al and Le et al used the BP obtained at the time of IgA nephropathy diagnosis, resulting in a relatively lower prevalence rate of hypertension as the measures were obtained early in the course of the disease [25, 28]. In contrast, we obtained our BP measures during a period of hospitalization due to deteriorating course of IgA nephropathy, which might account for the higher prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Many literature sources suggest that age is also a prognostic factor, and old age is correlated with poor prognosis [28, 29]. A previous study compared patients of different ages (≥ 50 and <50 years old) and found a higher incidence of arterial intimal thickening in the elder group, but no differences in the degree of other pathological changes; the follow-up for 41 months showed no difference in survival [30].…”
Section: Discussionmentioning
confidence: 99%
“…The predictors were verified in a group of patients with Henoch-Schonlein purpura. 55 Recently, Knoop et al 56 proposed the addition of eGFR and age to the ARR model to improve its prediction performance. The authors first validated ARR in 1134 IgA nephropathy patients (mean age 38 AE 16) from the Norwegian Kidney Biopsy Registry in the years 1988-2012.…”
Section: Iga Nephropathy In Elderly Patientsmentioning
confidence: 99%
“…Taken together, the existing data suggest that although the occurrence rate in the elderly based on the kidney biopsy differs between Europe/United States and Asia, IgA nephropathy in the elderly has generally similar clinical and histopathological characteristics. Compared with their younger adult counterparts, elderly patients tend to have a higher level of pre-existing comorbidity, higher degree of tubular interstitial fibrosis and vasculopathy on kidney biopsy, faster kidney progression despite treatment and, in two studies, 36,56 reduced patient survival.…”
Section: Iga Nephropathy In Elderly Patientsmentioning
confidence: 99%